A Scoping Review of Unmet Family Planning Needs in Young Couple: Effects of Socio-Demographic Factors, Parity, and Health Services - Pratami, Yustika Rahmawati; Yuliarti, Yayu; Pitasari, Nawang Wulan Nago (Jurnal Kesehatan Metro Sai Wawai, 2023)
Abstract Introduction: Young couples who have become mothers and do not have sufficient knowledge about family planning but are in the unmet need group for family planning have a higher risk of experiencing pregnancy complications. Pregnancy complications can lead to an increased risk of maternal mortality and morbidity. Purpose: This study explored the factors influencing the unmet need for family planning among young couples using the rapid review method. Methods: This scoping review study was sourced from ScienceDirect, Pubmed, and Wiley Online Library databases for article searches from 2010-2021. The primary study refers to young couples with unmet needs for a family planning group and explores its determinants, adapting the PRISMA-ScR 2020 checklist framework. Results: 14 articles met the inclusion criteria from 1,020 articles. The review found two determinants of unmet need for family planning among young couples: sociodemographic and health factors. Sociodemographic factors were divided into ten factors: age, place of residence, community culture, maternal motivation to participate in family planning, maternal autonomy in decision-making, knowledge, religion, marital status, economic status, and desire for family planning. Health factors are divided into two categories, namely parity and health services. Conclusion: The study found similar reasons for women's unmet family planning needs. The unmet need for family planning among young couples is common in developing countries. Latar Belakang: Pasangan muda yang telah menjadi Ibu dan tidak memiliki pengetahuan yang cukup tentang keluarga berencana, namun menjadi kelompok unmet need KB memiliki risiko lebih tinggi mengalami komplikasi kehamilan. Komplikasi kehamilan dapat menjadi penyebab peningkatan risiko kematian dan morbiditas ibu. Tujuan: Studi ini bertujuan mengeksplor faktor-faktor yang mempengaruhi unmet need KB pada pasangan muda dengan metode rapid review. Metode: Studi scoping review ini bersumber dari ScienceDirect, Pubmed, dan Wiley Online Library, sebagai database untuk pencarian artikel dengan rentang waktu 2010-2021. Kajian utama studi ini mengacu pasangan muda yang menjadi kelompok unmet need KB dan mengeskplorasi determinannya, mengadaptasi kerangka checklist PRISMA-ScR 2020. Hasil: Artikel ditemukan 14 yang memenuhi kriteria inklusi dari seleksi 1.020 artikel. Kajian telah menemukan dua faktor penentu unmet need KB pada pasangan muda, yaitu faktor sosio-demografi dan kesehatan. Faktor sosiodemografi dibagi menjadi 10 faktor yaitu umur, tempat tinggal, budaya masyarakat, motivasi ibu untuk megikuti Keluarga Berencana, otonomi ibu dalam pengambilan keputusan, pengetahuan, agama, status perkawinan, status ekonomi dan keinginan berKB. Sedangkan faktor kesehatan dibagi menjadi dua yaitu paritas dan pelayanan kesehatan. Simpulan: Studi menemukan alasan yang sama pada setiap perempuan yang kebutuhannya tidak terpenuhi padahal mereka membutuhkannya. Unmet need KB pada pasangan muda banyak dijumpai di negara-negara berkembang. Keadaan ini mengindikasikan bahwa fokus kontrasepsi di negara-negara berkembang harus ditingkatkan pada perempuan muda.